ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BPD KALIMANTAN TERHADAP PERBANKAN PERIODE 2011 – 2020 - Dede Hartanto Patarowo; Risal Rinofah; Pristin Prima Sari (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to study and understand the effect of CAR, BOPO and NPL simultaneously on Profitability in the form of ROA of the the Regional Development Bank Kalimantan for the period 2011 - 2020. Kalimantan Regional Development Bank for the period 2011 – 2020. The population used in this study is the Kalimantan Regional Development Bank from 2011 to 2020 which has complete and published financial reports. The type of data used in this research is secondary data. Purposive Sampling Sampling Technique,. Collecting data in this study using the method of documentation. The analysis technique used is multiple linear regression with a significance level of 5%. The results showed that the CAR partially positive and not significant effect on profitability (ROA). BOPO partially has a negative and significant effect on profitability (ROA). NPL partially has a negative and significant effect on profitability (ROA). CAR, BOPO and NPL together have an effect on Profitability (ROA).